Graphene Quantum Dots for Optical Bioimaging. Issue 36 (15th July 2019) - Lu, Huiting; Li, Wenjun; Dong, Haifeng; Wei, Menglian
Abstract: Graphene quantum dots (GQDs) have shown great potential in bioimaging applications due to their excellent biocompatibility, low cytotoxicity, feasibility for surface functionalization, physiological stability, and tunable fluorescence properties. This Review first introduces the intriguing optical properties of GQDs that are suitable for biological imaging, and is followed by the GQDs' synthetic strategies. The emergent and latest development methods for tuning GQDs' optical properties are further described in detail. The recent advanced applications of GQDs in vitro, particularly in cell imaging, targeted imaging, and theranostic nanoplatform fabrication, are included. The applications of GQDs for in vivo bioimaging are also covered. Finally, the Review is concluded with the challenges and prospectives that face this nascent yet exciting field. Abstract : The intriguing optical properties of graphene quantum dots (GQDs) suitable for bioimaging are introduced and followed by the GQDs' synthetic strategies. The emergent and latest developed methods for tuning GQD optical properties and recent advanced bioimaging applications of GQD are further described in detail. The challenges and prospective that face this nascent yet exciting field are discussed.